Highly Efficient Solution-Processed Blue Phosphorescent Organic Light-Emitting Diodes Based on Co-Dopant and Co-Host System - Jingyu Wang; Jiaxuan Yin; Xiaofang Li; Zhe Wang; Ruixia Wu; Liang Zhou (Molecules, 2022)
The low-lying HOMO level of the blue emitter and the interfacial miscibility of organic materials result in inferior hole injection, and long exciton lifetime leads to triplet-triplet annihilation (TTA) and triplet-polaron annihilation (TPA), so the efficiencies of blue phosphorescent organic light-emitting diodes (PhOLEDs) are still unsatisfactory. Herein, we design co-host and co-dopant structures to improve the efficiency of blue PhOLEDs by means of solution processing. TcTa acts as hole transport ladder due to its high-lying HOMO level, and bipolar mCPPO1 helps to balance carriers’ distribution and weaken TPA. Besides the efficient FIr6, which acts as the dominant blue dopant, FCNIrPic was introduced as the second dopant, whose higher HOMO level accelerates hole injection and high triplet energy facilitates energy transfer. An interesting phenomenon caused by microcavity effect between anode and cathode was observed. With increasing thickness of ETL, peak position of electroluminescence (EL) spectrum red shifts gradually. Once the thickness of ETL exceeded 140 nm, emission peak blue-shifts went back to its original position. Finally, the maximum current efficiency (CE), power efficiency (PE), and external quantum efficiency (EQE) of blue phosphorescent organic light-emitting diode (PhOLED) went up to 20.47 cd/A, 11.96 lm/W, and 11.62%, respectively.